THE INFLUENCE OF DEPOSITS FROM THIRD PARTIES CAPITAL ADEQUACY RATIO, AND NON PERFORMING LOANS AGAINST CREDIT DISTRIBUTION AT PRIVATE COMMERCIAL BANKS IN INDONESIA REGISTERED ON THE INDONESIA STOCK EXCHANGE IN 2015 – 2017 - Dwi Galih Budiharya, Elfreda Aplonia Lau, dan Murfat Effendi (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
This study aims to determine and analyze the partial influence andthe simultaneous influence of Deposit from Third Parties, Capital AdequacyRatio and Non Performing Loans on Credit Distribution in PrivateCommercial Banks in Indonesia Registered the Indonesia Stock Exchange in2015 to 2017The basic theory used in this study is financial management,especially regarding Third Party Funds, Capital Adequacy Ratio, and Non-Performing Loans. The analysis technique used in this study is multiplelinear regression. The use of multiple linear regression requires the testingof classic assumptions and linearity.The results showed that simultaneously Third Party Funds, CapitalAdequacy Ratio, and Non-Performing Loans had a significant effect onlending to private commercial banks in Indonesia which were listed on theIndonesia Stock Exchange. Partially, Third Party Funds have a significantpositive effect on lending, Capital Adequacy Ratio has a significant negativeeffect on lending, and Non-Performing Loans have a non-significant positiveeffect on lending